Viral immunity: cross-priming with the help of TLR3. - Salio, M; Cerundolo, V (2005)
Cross-presentation is important for regulating T-cell responses to exogenous antigens and can maintain tolerance (cross-tolerance) or induce immune responses (cross-priming). Recent exciting results on the role of the Toll-like receptor TLR3 in promoting cross-priming of viral antigens provide new insights into the mechanisms that allow Toll-like receptor signaling to bridge innate and adaptive immune responses.